Associations and interactions of the serotonin receptor genes 5-HT1A, 5-HT2A, and childhood trauma with alexithymia in two independent general-population samples. (April 2021) - Terock, Jan; Weihs, Antoine; Teumer, Alexander; Klinger-König, Johanna; Janowitz, Deborah; Grabe, Hans J.
Highlights: Data from two independent samples of the general population (N=3, 706 and N=2, 162) were used We tested whether rs6295 of the 5-HT1A gene and rs6311 of 5-HT2A were associated with alexithymia We also tested if these polymorphisms interacted with childhood trauma in their effects on alexithymia No main effects of the tested polymorphisms were detected Significant childhood trauma x rs6295 effects on alexithymia in male subjects were found in both samples Abstract: Previous studies suggested that childhood trauma and a disturbed serotonergic neurotransmission are involved in the pathogenesis of alexithymia. Specifically, genetic polymorphisms of the serotonin receptors 5-HT1A and 5-HT2A were found to be associated with alexithymia. However, it is unclear whether these factors show main or interaction effects with childhood trauma on alexithymia. Data from two independent general-population cohorts of the Study of Health in Pomerania (SHIP-Trend: N=3, 706, Age: range=20-83, 51.6% female, SHIP-LEGEND: N=2, 162, Age: range=20-80, 52.5% female) were used. The Toronto Alexithymia Scale-20 (TAS-20) and the Childhood Trauma Questionnaire (CTQ) were applied. Genotypes of rs6295 of 5- HT1A and rs6311 of 5 - HT2A were determined. Ordinary least-squared regression models with robust standard errors were applied to investigate associations of the main and interaction effects of childhood maltreatment and the polymorphisms with alexithymia. Childhood trauma, but none of the investigated polymorphisms showed main effects on alexithymia. However, childhood trauma showed significant CTQ sum score x rs6295 interactions in male subjects in both samples such that the presence of the G-allele diminished the CTQ associated increase in the TAS-20 sum scores. Our results support a strong role of early life stress and interactions with rs6295 on alexithymic personality features at least in male subjects.